2020
DOI: 10.17533/udea.iee.v38n3e09
|View full text |Cite
|
Sign up to set email alerts
|

Communication in health work during the COVID-19 pandemic

Abstract: Objective. Report on communication and qualified listening in nursing work in the face of the COVID-19 pandemic. Methods. This descriptive, theoretical and reflexive report was developed by nurses between March 20th and May 25th 2020 at Emergency Care Services in the city of Fortaleza, Ceará, Brazil. Health communication served as the theoretical background for this research. Results. Two main thematic categories were highlighted: (i) Resignifications of communication in the work relationships of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 18 publications
0
28
0
3
Order By: Relevance
“…The main goal of HCO was considered to provide high-quality care to patients and meet their needs and expectations during an outbreak such as COVID-19 [ 96 ]. Moreover, dialog and listening to health demands in COVID-19-suspected patients was highlighted as the foremost step in the flows of care and guidance [ 134 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main goal of HCO was considered to provide high-quality care to patients and meet their needs and expectations during an outbreak such as COVID-19 [ 96 ]. Moreover, dialog and listening to health demands in COVID-19-suspected patients was highlighted as the foremost step in the flows of care and guidance [ 134 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main goal of HCOs was considered to provide high-quality care to patients and meet their needs and expectations during an outbreak like COVID 19 [100]. Moreover, the importance of dialogue and listening to health demands in COVID-19-suspected patients was highlighted as the main step in the flows of care and guidance [109].…”
Section: The Responsiveness and Communication Dimension In Covid-19mentioning
confidence: 99%
“…47 Norful et al 48 observed that nurses' communication and empathy skills declined as their workload increased and that good communication skills were associated with better performance. In another ED study, Rodrigues et al 49 reported that after trainings and meetings to improve nursing care activities and restructure communication among the staff, ED dynamics improved significantly and the health care team demonstrated better cooperation and harmony. In a quasiexperimental study conducted with nursing students and aiming to enhance emergency response capability, quality communication and having up-to-date information improved the students' professional development and had a favorable impact on their practitioner roles.…”
Section: Discussionmentioning
confidence: 99%